2016
DOI: 10.1002/mds.26670
|View full text |Cite
|
Sign up to set email alerts
|

Appendectomy in mid and later life and risk of Parkinson's disease: A population‐based study

Abstract: In our study, appendectomy in mid or late life does not appear to be associated with a reduced risk of PD. © 2016 International Parkinson and Movement Disorder Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 13 publications
0
42
1
Order By: Relevance
“…One intriguing possibility is that gastrointestinal inflammation caused by infections or ulcers could predispose to α‐syn aggregation. Recently, we and another research group showed that appendectomy carries an increased risk of subsequent PD . Again, a possible interpretation is that the inflammatory state (ie, appendicitis) preceding the appendectomy increases the risk of initiating the α‐syn aggregation cascade.…”
Section: Protective Effect Of Vagotomymentioning
confidence: 96%
See 1 more Smart Citation
“…One intriguing possibility is that gastrointestinal inflammation caused by infections or ulcers could predispose to α‐syn aggregation. Recently, we and another research group showed that appendectomy carries an increased risk of subsequent PD . Again, a possible interpretation is that the inflammatory state (ie, appendicitis) preceding the appendectomy increases the risk of initiating the α‐syn aggregation cascade.…”
Section: Protective Effect Of Vagotomymentioning
confidence: 96%
“…Recently, we and another research group showed that appendectomy carries an increased risk of subsequent PD. 110,111 Again, a possible interpretation is that the inflammatory state (ie, appendicitis) preceding the appendectomy increases the risk of initiating the a-syn aggregation cascade. At the moment, this hypothesized association between gut inflammation/infection and a-syn aggregation remains speculative, but the novel findings that native a-syn may inhibit the access of neuro-invasive viruses to the CNS could be involved.…”
Section: Protective Effect Of Vagotomymentioning
confidence: 99%
“…162 While the history of appendectomy was associated with delayed onset of PD symptoms in a small late-onset cohort 163 a larger study found no effect, 164 and others find either no effect or a slightly increased risk of developing PD 5-10 years postappendectomy. 165,166 As a reservoir of microbes and immune cells, the appendix could still have a role in modulating PD risk by influencing microbial and immune homeostasis. Given the interaction between gut microbes, enteroendocrine cells, enteric neurons and the enteric immune system discussed above, and recent evidence that bacterial proteins can enhance αSyn aggregation in animal models, 167 the activities of specific gut microbes or a more general 'microbial dysbiosis' could conceivably play a role in the transition from benign to pathogenic αSyn states.…”
Section: Microbiota-gut-brain Pathways In Neurodegenerative Diseasementioning
confidence: 99%
“…In an analysis of the Danish National Registry, with 34 years of follow‐up, appendectomy was associated with a modest 15% increase (95% CI, 3%‐27%) in PD risk . In contrast, no association between appendectomy and PD risk was found in a registry‐based study in Ontario, Canada, comparing 42,999 participants with appendectomy with those with cholecystectomy or no procedures …”
mentioning
confidence: 99%
“…18 In contrast, no association between appendectomy and PD risk was found in a registry-based study in Ontario, Canada, comparing 42,999 participants with appendectomy with those with cholecystectomy or no procedures. 19 In this study, we sought to examine the association between self-reported appendectomy and incidence of PD in 2 large prospective cohort studies, the Nurses' Health Study and the Health Professionals Follow-up Study.…”
mentioning
confidence: 99%